Hukum Sebagai Senjata Politik dan Fenomena Viralitas Sebagai Senjata Sosial - Aswin, Albert Stephan; Faisal, Sarman; Husain, Alwi (Jurnal Bedah Hukum, 2025)
This writing explores the use of law as a political tool by populist authoritarian leaders in Indonesia, who often enforce it selectively to suppress opposition and protect political allies, undermining the principles of justice and the rule of law. Through the phenomenon of "No Viral, No Justice," the public has actively pressured law enforcement agencies to act in accordance with principles of justice, although this sometimes shifts the enforcement of the law from its ideal path. The research method employed is qualitative, using document analysis to evaluate this social phenomenon. The discussion in this paper illustrates that the weakening of the KPK through amendments to the KPK Law and its use as a tool by those in power is a clear example of legal abuse by populist authoritarian leaders. In this context, the principle of "Equality Before the Law" is neglected, resulting in the public resorting to viral campaigns to demand justice. While the viral phenomenon highlights shortcomings in the legal system, the enforcement of law based on the rule of law must still be upheld to ensure equitable justice and prevent abuse of power. In conclusion, the phenomenon of "No Viral, No Justice" has become an important tool for the public to ensure that the law is not used arbitrarily by those in power but is instead applied fairly to all parties. The viral phenomenon demonstrates that the public can control law enforcement and play a significant role in promoting justice, even though the principle of the rule of law remains the fundamental basis for maintaining the integrity of the criminal justice system.